Argentina : Una república democrática ¿Ficticia o real? - Frenkel, Natalia (2009)
The delegation of legislative powers, unlike the other institutions introduced\nby virtue of the 1994 constitutional amendment, is still subject to both\npolitical and theoretical debate. By analyzing its features, we intend to determine\nits legitimacy according to the principles set forth in our Constitution. In this\nwork, emphasis will be laid on the delegation of legislative powers to the Chief\nMinister (Jefe de Gabinete) pursuant to the Financial Administration Act (Ley de\nAdministración Financiera) - the constitutionality of which is being challenged.\nUnder this law, said Minister is authorised, for instance, to reassign budget items.\nNot only is compliance with our Constitution being questioned, but also the basis\nof our government?s organization: the Republic